1996
DOI: 10.1046/j.1365-2796.1996.413755000.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for diabetic retinopathy in South Africa with 60° retinal colour photography

Abstract: 60 degrees retinal photography compares well with an ophthalmologists screening, and is better than clinical and one to two 45 degrees field assessments. Both retinae should be screened. This method is cost-effective in our hands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
0
20
2
Order By: Relevance
“…Other studies have shown that photos without mydriasis were often of poor quality and unable to be graded, especially in older patients and in the presence of media opacities 18 , 19 . The higher failure rate of fundus photography in our study (11%; 86/792) compared with the reported failure rate of dilated fundus photography (4%–8%) 14 16 , 18 may have resulted from a higher prevalence of media opacities, such as corneal scarring and cataract, among Indigenous Australians 23 . Media opacity or small pupils would increase the likelihood of a false negative result, reducing the sensitivity of the screening photography.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Other studies have shown that photos without mydriasis were often of poor quality and unable to be graded, especially in older patients and in the presence of media opacities 18 , 19 . The higher failure rate of fundus photography in our study (11%; 86/792) compared with the reported failure rate of dilated fundus photography (4%–8%) 14 16 , 18 may have resulted from a higher prevalence of media opacities, such as corneal scarring and cataract, among Indigenous Australians 23 . Media opacity or small pupils would increase the likelihood of a false negative result, reducing the sensitivity of the screening photography.…”
Section: Discussioncontrasting
confidence: 70%
“…The presence and degree of DR was graded using the Early Treatment of Diabetic Retinopathy Study (ETDRS) adaptation of the modified Airlie House classification of DR 12 by clinical comparison with standardised photographs (Box 1). The DR was graded as either no DR (level 10-13), minimal non-proliferative DR (NPDR) (level [14][15][16][17][18][19], mild NPDR (level 20-39), moderate NPDR (level 40-49), severe NPDR (level 50-59) and proliferative DR (PDR) (level 60-85). Clinically significant macular oedema (CSMO) was defined as any retinal thickening within 500 μm of the fovea associated with retinal thickening that is at least one disc area in size within one disc diameter of the fovea.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetic retinopathy in Africa • P. I. Burgess et al Not reported *Three reports [31,35,60] described grades of diabetic retinopathy in overlapping populations. Figure for any diabetic retinopathy taken from the largest report [31] (n = 1517); associations of diabetic retinopathy taken from smaller report (n = 507) [35].…”
Section: Diabeticmedicinementioning
confidence: 99%
“…Screening using retinal photography has been piloted [26,27,29]. However, most reports have come from South Africa and these efforts have largely been initiated by local hospitals or by external funding and support.…”
Section: Discussionmentioning
confidence: 99%
“…Defining an eligible population is an essential component of a screening program but is another challenge in resource-poor settings. Apart from rudimentary costing [26], no evidence on cost effectiveness of screening programs on the continent is available. The fact that patients present late with diabetes must be considered.…”
Section: Discussionmentioning
confidence: 99%